2005
DOI: 10.1103/physrevb.72.205203
|View full text |Cite
|
Sign up to set email alerts
|

Relative bulk and interface contributions to optical second-harmonic generation in silicon

Abstract: Using the simplified bond-hyperpolarizability model, we obtain analytic expressions for the first-forbidden ͑spatial dispersion, magnetic dipole/electric quadrupole͒ bulk contributions to second-harmonic generation for centrosymmetric materials. Applying these to oxidized Si, we show theoretically and by comparison to experiment that the relative bulk contribution near 800 nm is minor, less than half that of the interface, but that the coherent superposition of bulk and interface contributions is important and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…On the basis of the 58 vicinal (111) Si data, Lüpke et al [9] and McGilp [31] both concluded that the bulk contribution is significant. In contrast, in fitting lineshapes to data, and in particular examining the 98 vicinal results where the third-and fourth-rank tensor separation should be more distinct, Peng et al [27] came to the opposite conclusion. They pointed out that additional information could be obtained from the 7th harmonic, which is nonzero only if both third-rank and bulk forth-rank tensor contributions are present.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…On the basis of the 58 vicinal (111) Si data, Lüpke et al [9] and McGilp [31] both concluded that the bulk contribution is significant. In contrast, in fitting lineshapes to data, and in particular examining the 98 vicinal results where the third-and fourth-rank tensor separation should be more distinct, Peng et al [27] came to the opposite conclusion. They pointed out that additional information could be obtained from the 7th harmonic, which is nonzero only if both third-rank and bulk forth-rank tensor contributions are present.…”
mentioning
confidence: 91%
“…Given the above success, we applied the same basic approach to fourth-harmonic generation (FHG) at the Si-SiO 2 interface [25], and third-harmonic (THG) [26] and dipole-forbidden SHG [27] from bulk Si. The FHG work, done with the objective of interpreting data obtained by the Downer group on surfaces of varying roughness [28], showed that interface angles were not always those of the bulk, a result also found by Kwon et al [5] Our most recent application, to amorphous (a-) SiO 2 [14], was intended as a first step toward understanding the data of Figliozzi et al [29] on crystalline Si nanoparticles embedded in SiO 2 .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, in this paper, we generalize the SBHM to a more complete description, the anisotropic bond model ͑ABM͒, which includes charge motion transverse to the bond, RD, SD, and MG effects, including SD effects arising from beam geometry, and SHG signals for off-axis observation angles, i.e., the role of diffraction. In developing our expressions, we follow the approach of Peng et al, 8 framing the calculations in terms of the fundamental four-step process of optics: ͑1͒ evaluate the local field at any given charge site that results from the driving ͑source͒ field, ͑2͒ solve the mechanical equation F ជ = ma ជ to obtain the acceleration of the charge, ͑3͒ calculate the radiation that results from the acceleration, and ͑4͒ superpose the radiation from all contributing charges. For random media, we show that step ͑4͒ factors into two parts: ͑4a͒ average over all possible bond orientations at a single site, and then ͑4b͒ calculate the properties of the emerging beam by Fourier transforming the envelope function of the incident radiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the intervening years since this debate first took place a consensus has developed among researchers that materials like Si are characterized by intrinsic nonlinear surface anisotropy with surface dipolar and bulk quadrupolar sources [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] divided in almost equal parts. In Ref.…”
Section: Introductionmentioning
confidence: 99%